Dielectric Response of ZnTe–Ti/Al Schottky Junctions with CdTe Quantum Dots Studied by Impedance Spectroscopy - Eunika Zielony; Ewa Płaczek-Popko; Grzegorz Karczewski (Crystals, 2020)
The electrical properties of ZnTe−Ti/Al Schottky junctions were investigated by the impedance spectroscopy (IS) method. Current-voltage (I-V) and capacitance-voltage (C-V) measurements were also performed. The studied samples were the CdTe quantum dot structures embedded in ZnTe matrix and a reference ZnTe sample without quantum dots. C-V characteristics confirmed the presence of quantum dots (QDs) in the structures. Electric modulus and impedance data were analyzed. IS studies proved that long-range conductivity governs the relaxation processes in the junctions. For both samples, the data were fitted with a simple RC circuit composed of a depletion layer capacitance in parallel with bulk resistance and a series resistance of contacts. The activation energy of the relaxation process observed for the reference sample obtained from the Arrhenius plot of the resistance, imaginary impedance, and electric modulus equals 0.4 eV at zero bias. For the quantum dot sample, the value of activation energy determined with the help of the same methods equals 0.2 eV. In conclusion, it was assumed that the relaxation processes for the reference sample are attributed to the trap present in ZnTe host material, whereas those observed for the QD structure are assigned to the deep level associated with defects located close to the QDs created during their growth.